Post-and-Core Restorations with 3D Technologies: Benefits and Limitations - Gurskaya, Narmina Azad (Actual Dentistry, 2026)
Post-and-core restorations in prosthetic dentistry are employed to replace defects in hard dental tissues, aiming to preserve the integrity and function of the dental arch while achieving superior esthetic outcomes. When appropriately applied as supports for artificial crowns, these restorations maintain the tooth root and provide high esthetic quality and functionality, thereby enhancing the overall effectiveness of prosthetic treatment. Polymer-based post-and-core restorations fabricated through additive manufacturing have become an essential component of modern dental practice. They play a pivotal role in rehabilitating severely compromised teeth following endodontic treatment. The application of 3D-printed polymer restorations demonstrates considerable promise for advancing tooth-preserving technologies.